Migration, Taxation, and Inequality - Moreno-Dodson, Blanca (World Bank, Washington, DC, 2012)
International migration is intimately intertwined with issues of taxation, inequality and public welfare benefits, both in home and destination countries. In home countries the emigration of workers, especially high-skilled workers, is often perceived to create a fiscal loss due to the cost of educating these workers and foregone tax revenues that may reduce the fiscal resources available for income redistribution. On the other hand, remittances, when well spent, can create multiplier effects and contribute to increasing domestic demand and growth, as well as increasing tax collections. In destination countries, immigration raises other challenges, especially when poor and undocumented workers are perceived as taking more from the government budget in the form of social welfare and health care benefits than what they contribute in the form of tax revenues. This note discusses some of the current issues around migration and taxation including how to compensate home countries for the fiscal losses of high-skilled emigration, how to bring immigrants into the tax system and make them net contributors, whether or not to tax inward, cross-border remittances, and designing appropriate tax incentives to encourage diaspora investment in the home country.